Health seeking attitude of women regarding reproductive tract infections in a rural area of Surendranagar district - Thekdi, Komal P.; Patel, Nita K.; Patel, K. G.; Thekdi, Pukur I. (International Journal of Research in Medical Sciences, 2017)
Background:In the recent years, the issue of gynaecological problems of poor women in the developing countries has been receiving increasing attention. High levels of gynaecological morbidity, especially reproductive tract infections and sexually transmitted infections may turn out to be fatal if not treated properly. The objective of this study was to assess the health seeking attitude of women regarding reproductive tract infections, to elicit the past history pertaining to it, to assess the personal hygiene measures relevant to it. Methods: Various community based studies carried out in the different regions world showed the prevalence of reproductive tract infections 36-84%. The sample size of study as per statistical calculation (4pq/l2, where p =50, q=100-p and l= 10% of p) came out to be 400. Prior enlisting all villages of Surendranagar district, one village was selected randomly. After random selection the village found was Khodu. Results: 75.3% of women narrated treatment was necessary; 44% told that preferably to be taken from doctor and 24.7% told treatment should not be taken because of social and personal reason. 56.5% of women having one or the other kind of symptom of reproductive tract infections. Women with poor menstrual and personal hygiene has got 2.5 times chances of reproductive tract infections (OR= 2.35, CI= 1.374-4.01, P value: 0.001). Thus the overall prevalence in our study is 56.5%. On statistical analysis it was found that women who used clothes were two times more symptomatic as compared to women who used sanitary pads, a significant association between women having symptoms of reproductive tract infections and their sexual history. The present study showed 61.94% of women had taken treatment which shows that the health seeking behavior had improved. Conclusions: Women who used sanitary pads during menstrual periods had lower prevalence. Women with complaints of dyspareunia, bleeding during and or after intercourse and history of forceful intercourse had maximum prevalence of reproductive tract infections. 19.8% of women gave past history of reproductive tract infections and out of that 15.16% of women had taken treatment for it. Regarding health seeking attitude of symptomatic women, 61.94% of women had taken treatment and majority of them had taken treatment from doctors. This implies that health intervention measures directed towards reducing morbidity from reproductive tract infections need not focus mainly on treatment of reproductive tract infections but rather on disease preventing strategies.